The slightly’ changes of occupation pattern, education, health and social behaviour: An Ethnographic insight in the age of Covid - Chinmay Biswas (Ridwan Institute, 2023)
The present paper has tried to discuss what “smart ethnography” is. It has endeavoured to focus on the current situation of ethnography in this pandemic time to some extent. Sitting at a computer desk, what we have seen, through the lenses of Smartphones, media coverage, and daily newspapers, what we observed, as a student of anthropology, is written in this paper. According to the view of social anthropology, this type of equipment has been regarded as the ultimate essential technological device for investigating human behaviour in a pandemic situation. At the beginning of the essay, remember that if we go back to armchair anthropology before Malinowski, where anthropologists had collected data from travellers and other sources, in the present situation, data is collected from the newspaper, the Internet, research papers, webinars, and mobile phones from the opposite side of the devices-the participant may be a respondent. Therefore, the concept of a researcher, or else fieldworker, and respondent slightly has changed under this pandemic situation due to the social distancing or physical distancing. The present paper discusses these issues at an initial stage.